Study of the Knowledge and Content Flows of Articles in the Journal of Accounting Knowledge from the Beginning of the Publication to the end of 2019 - Maryam Nobakht; Younes Nobakht (بازیابی دانش و نظام‌های معنایی, 2021)
Content analysis of journals by identifying the characteristics of the information recorded in the articles helps the editors of the journals to identify the strengths and weaknesses of the journal. The objective of this research is to study the knowledge and content flow of articles in the journal of accounting knowledge as one of the most prestigious scientific publications in the field of accounting knowledge in Iran from the beginning of 2005 to the end of 2019. This research is a scientometrics study and using the content analysis method (quantitative approach). The population of the study consisted of all the articles published in the journal that were all selected as a statistical sample. The research data were also collected using a checklist tool and statistical analysis using Excel software. Findings of the research show that in 285 articles published during these years, 696 authors have contributed, of which MA degree with 34% and assistant professors with 30% are at the top of the table are the authors of this journal. Among the universities and educational institutions, Shiraz University is ranked first with 25 articles, and the University of Tehran is ranked second with 34 articles. In terms of topic orientation, 83% of the publications are in the field of financial accounting and auditing with 10% in the next rank. From the total 8179 references cited in the articles, 73% were in English and 27% in Persian.